HUBUNGAN KEPEMIMPINAN PEMBELAJARAN DAN KECERDASAN EMOSIONAL KEPALA SEKOLAH DENGAN MOTIVASI BERPRESTASI GURU SMP - Rusdiana, Erin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to reveal the relationship of leadership leadership and emotional intelligence of the principal with teacher achievement motivation, the population in this study is the junior high school teachers in Sub Rayon XI Sebawi Sambas Regency amounted to 77 people consisting of teachers: SMPN 1 Sebawi as many as 27 people, SMPN 2 Sebawi as many as 20 people, SMPN 3 Satap Sebawi as many as 9 people, SMPN 4 Satap Sebawi as many as 8 people, SMPS budas Harapan sebawi as many as 13 people. The instrument used is questionnaire. The results showed that the relationship of leadership leadership and emotional intelligence of the principal with the achievement motivation of junior high school teachers in Sub Rayon XI Sebawi Sambas District, belong to very good and very significant category. The results of this study can be useful for the principal is to continue to improve leadership learning and emotional intelligence, and for teachers to continue to improve motivation berprestasinya. . Â Keywords: Leadership, Emotional Intelligence, Motivation.